Biosurfactant production by utilizing waste products of the food industry - Alara, Oluwaseun Ruth; Abdurahman, Nour Hamid; Ali, Hassan Alsaggaf (Academic Press, 2023)
The interest in the use of biosurfactants has continued to improve over the years because of their environmentally friendly nature, diversity, the alternative of production through fermentation, and potential usages in food processing, healthcare, crude oil recovery, and environmental protection that includes bioremediations of a site contaminated with heavy metals and polychlorinated biphenyls. Nevertheless, the economic viability of biosurfactants with their counterparts (synthetic surfactants) requires adequate processing during production. Therefore, this chapter unveils some of the wastes from the food industry with potential use in the production of biosurfactants. These include wastes from agri-food, cooking oils, brewery, animal wastes from the food industry, bakery and dairy, lignocellulosic, and starch-rich wastes.